2010
DOI: 10.1002/mds.23152
|View full text |Cite
|
Sign up to set email alerts
|

Psychometric attributes of the rating scale for gait evaluation in Parkinson's disease

Abstract: Metric attributes of the RSGE-PD-V2.0 in this sample of study resulted in has sufficient and suitable satisfactory. We, therefore, believe that RSGE-PD-V2.0 is easy and a useful and recommendable specific tool for measuring gait disease in PD patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 35 publications
0
6
0
Order By: Relevance
“…No floor or ceiling effects were found . Internal consistency of the total scale is high; item‐total correlations of separate items ranged from 0.39 to 0.84.…”
Section: Resultsmentioning
confidence: 78%
See 2 more Smart Citations
“…No floor or ceiling effects were found . Internal consistency of the total scale is high; item‐total correlations of separate items ranged from 0.39 to 0.84.…”
Section: Resultsmentioning
confidence: 78%
“…The developers of the Rating Scale for Gait Evaluation (RSGE) recommend using version 2.1), which contains 21 items grouped in 4 subscales (functional ability, long‐term complications, socioeconomic conditions and examination). The scale has been used in at least 5 PD studies . It is administered by a clinician and available in Spanish and English.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies found that CISI-PD explains 92% of the CGIS variance and as a whole, correlated at higher level than other global measures with a diversity of scales assessing a diversity of PD-related manifestations and consequences. 9,10,17,18 …”
Section: Discussionmentioning
confidence: 99%
“…As cognitive symptoms in PD clearly differ from AD symptoms, it was more and more realised that AD-related assessment tools have relevant flaws in determining cognitive dysfunction in PD, and effort has been put into the development of sensitive and reliable PD-relevant measurement tools. One of the most promising tools is the “Scales for outcomes in Parkinson’s disease-cognition (SCOPA-COG)” having advantages as compared to the MMSE, the most important having a greater discriminative capacity (Serrano-Duenas et al 2010); however, longitudinal studies are not yet available.…”
Section: Clinical Biomarker Candidatesmentioning
confidence: 99%